Teacher Educators’ Perceptions about Continuing Professional Development - Tyagi, Chanchal; Misra, Pradeep Kumar (JOURNAL OF INDIAN EDUCATION, 2019)
The present paper aims to study teacher-educators’ perceptions about different aspects of Continuing Professional Development (CPD) and also compares their perceptions with respect to teaching experiences and nature of serving institutions. The study was conducted on 97 teacher educators’ serving in different aided and self-financed colleges of teacher education institutions and teaching to students of B.Ed. and M.Ed. Data was collected through a questionnaire developed and standardised by the researchers. Findings revealed that for majority of teacher educators, CPD is similar to INSET (InService Teacher Education) programmes and different INSET activities like workshop, seminars, and training programmes are main part of their CPD learning and experiences. Majority of the respondents also reported that they cannot practice CPD without institutional and governmental support. Besides, no significant differences were found in teacher educators’ perceptions with respect to their teaching experiences and nature of serving institution.